Creating the New Worker Work, Consumption and Subordination - Durand, Jean-Pierre (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores the relationship between the changing nature of capitalism and the creation of the new worker. In a changing global economy, work - as the activity that structures individuals in capitalism both socially and psychologically - is being undermined. Combining a Gramscian critique of contemporary patterns of capitalist labour control with Lacanian psychoanalysis, Durand examines what kinds of human beings are emerging in and through modern work, or on its margins. Creating the New Worker will be of interest to students and scholars who engage in the sociology and psychology of work, economics, and labour. .